Risk Analysis of Contractor Selection in Construction Work Procurement - Putri, Dinda Rahmi; Ophiyandri, Taufika; Hidayat, Benny (Universitas Negeri Padang, 2024)
This research is about the risk analysis of the selection of contractors in the procurement of construction works. The method used to carry out the existing risk analysis is the Failure Mode and Effect Analysis method. The research was conducted on five Work Units for Procurement of Goods and Services (UKPBJ) with the highest number of failed tenders from 2021 to 2022. Risk identification was carried out by means of literature studies and pilot surveys in the form of interviews with several selection working groups. It was found that there were 26 risks to be analyzed. Data collection was carried out by distributing questionnaires to the selection working group, where the selection working group was asked to fill in the levels of severity, occurrence, and detection for the 26 existing risks. Then analyzed using the RPN method for each risk. The results obtained show that of the 26 existing risks, there are 10 that have an RPN value above the critical value. These risks are delays in procurement preparation documents from PPK SKPD, failed auctions, qualification results that are not the actual ability of participants, shortage of uploading tender documents, goods and services providers not interested in participating in the auction, objections or complaints from bidders, misunderstanding of information in the auction, Details of HPS known by bidders, Intimidation from Providers, NGOs, and law enforcement officials, and Mistakes in choosing a provider Then the level of importance of the risk is also determined by multiplying the frequency with the impact so that there is one risk that is at a moderate level, namely the risk of delay in procurement preparation documents from PPK SKPD. For the ten risks that are above the critical value, mitigation measures are carried out in order to minimize the impact that occurs.